He-Ne Monochromatic Light with Selenium nanoparticles as Medical Technique - Hassan Tuhmaz (Journal of Global Pharma Technology, 2016)
In this study, the photo-thermal dealing of cancer with Se nanoparticles is studied. This processes for tissue under the influence of heat by a laser source with dose injection the selenium nanoparticles on the affected area. The bio-heat equation is solved by numerical simulation methods. Results are summarized in the effect on the increase of temperature at different time stages. These results appeared that the depth diffusion increasing heat raising during the increasing the time duration of exposure. Thus, it concludes the peak value of depth with controlled temperature.Keywords: Selenium nanoparticles; Heat raising; Medical technique.